Plasminogen activator inhibitor-1 promotes immune evasion in tumors by facilitating the expression of programmed cell death-ligand 1 - Ibrahim, Abd Aziz; Fujimura, Taku; Uno, Tomoko; Terada, Tomoya; Hirano, Ken-ichi; Hosokawa, Hiroyuki; Ohta, Akio; Miyata, Toshio; Ando, Kiyoshi; Yahata, Takashi (Frontiers in Immunology, 2024)
Background Increased levels of plasminogen activator inhibitor-1 (PAI-1) in tumors have been found to correlate with poor clinical outcomes in patients with cancer. Although abundant data support the involvement of PAI-1 in cancer progression, whether PAI-1 contributes to tumor immune surveillance remains unclear. The purposes of this study are to determine whether PAI-1 regulates the expression of immune checkpoint molecules to suppresses the immune response to cancer and demonstrate the potential of PAI-1 inhibition for cancer therapy. Methods The effects of PAI-1 on the expression of the immune checkpoint molecule programmed cell death ligand 1 (PD-L1) were investigated in several human and murine tumor cell lines. In addition, we generated tumor-bearing mice and evaluated the effects of a PAI-1 inhibitor on tumor progression or on the tumor infiltration of cells involved in tumor immunity either alone or in combination with immune checkpoint inhibitors. Results PAI-1 induces PD-L1 expression through the JAK/STAT signaling pathway in several types of tumor cells and surrounding cells. Blockade of PAI-1 impedes PD-L1 induction in tumor cells, significantly reducing the abundance of immunosuppressive cells at the tumor site and increasing cytotoxic T-cell infiltration, ultimately leading to tumor regression. The anti-tumor effect elicited by the PAI-1 inhibitor is abolished in immunodeficient mice, suggesting that PAI-1 blockade induces tumor regression by stimulating the immune system. Moreover, combining a PAI-1 inhibitor with an immune checkpoint inhibitor significantly increases tumor regression. Conclusions PAI-1 protects tumors from immune surveillance by increasing PD-L1 expression; hence, therapeutic PAI-1 blockade may prove valuable in treating malignant tumors.